DAMPAK PENURUNAN KELAS MENENGAH TERHADAP KONSUMSI RUMAH TANGGA DAN PERTUMBUHAN EKONOMI - Cici Ananta Siagian; Putri Nurul Zulia Lubis; Sabrina Noor Wijaya (Cahaya Ilmu Bangsa, 2025)
This article discusses the important role of the middle class in the Indonesian economy and the impact of its decline on household consumption and economic growth. The middle class is considered the main driver of economic growth, contributing significantly through high consumption and entrepreneurship that creates jobs. This research shows that a larger proportion of the middle class is associated with faster economic growth, and that a decline in the size of the middle class, especially due to the impact of the COVID-19 pandemic, could result in increased social and economic instability. Using a qualitative approach and literature study, this article highlights the urgency of government policy support to strengthen the middle class through creating quality jobs, improving education, and access to investment. These findings emphasize that the existence of a strong and growing middle class is key to achieving inclusive and sustainable economic growth in Indonesia, as well as the importance of greater attention to the middle class in the formulation of economic policies.